RUSSIAN BOWS THROUGH CENTURIES - E. B. Morozova (Концепт: философия, религия, культура, 2019)
The article looks at semantic and pragmatic changes on gesture “bow” in the Russian language and culture throughout 11th – 21st centuries. The paper analyses four types of bows (a prostration, bow from the waist, polite bow and a nod) and three contexts of their usage – religious, ritual and secular. The study demonstrates that throughout the given period the semantics and pragmatics of the gesture have gradually been narrowing. It is in the religious context where we still fnd two original forms of stooping used. Starting from the reign of Peter the Great new types of ceremonial bows were borrowed from Europe, but practically disappeared in the 1920-s after social classes system was banned by new Socialist government. At present we can observe the use of bows in Russian diplomatic protocol and in the theatre or other performances. The sphere of secular bows initially had only two forms, embracing new ones in the second half of the 17th century. Nowadays almost all of them have passed out of use. The fndings clearly indicate that by the 21st century Russian gesture “bow” have lost most of its meanings, and their usage has signifcantly decreased.